High-fidelity immersive virtual reality environments for gait rehabilitation exergames - Schalbetter, Laura; Grêt-Regamey, Adrienne; Gutscher, Fabian; Wissen Hayek, Ulrike (Frontiers in Virtual Reality, 2025)
Virtual reality (VR) used for healthcare, particularly through exergames, is promising for improving therapeutic outcomes. However, effectively engaging patients and providing realistic environments for everyday situations remain major challenges. The technical aspects of developing engaging VR applications for rehabilitation are largely unexplored. This research presents the development of a head-mounted display VR (HMD-VR) exergame for gait therapy. The novelty lies in the use of high-fidelity immersive environments implementing 3D geospatial data and motion to create targeted therapeutic applications that closely mimic reality while harnessing the environment's restorative functions. We integrated 3D point clouds from laser scans and geolocated ambisonic sound recordings into a game engine. We combined different techniques for user motion tracking, while we used point cloud manipulation for integrating specific training elements. Feedback on the quality of the HMD-VR exergame was received from the first implementations. Our methodology demonstrates the successful, highly realistic VR replication of restorative real-world environments using 3D point clouds and environmental sounds. We illustrate the adaptability of the environment for therapeutic use through manipulation of the 3D point cloud, facilitating customizable training difficulty levels while promoting immersive experiences. Participant feedback (sample size: 49 sessions) confirms the HMD-VR exergame's applicability as a restorative experience (ClinicalTrials.gov XXX). Our research introduces a pioneering HMD-VR game for gait rehabilitation, leveraging immersive VR environments grounded in the real world. This innovative approach offers new possibilities for efficient and effective rehabilitation interventions. Future studies will analyze effects on gait patterns across different environments and their restorative functions and evaluate the HMD-VR exergame in clinical settings.